THE PEOPLE'S REJECTION OF PROPHETIC MESSAGES AND LEGISLATION IN THE FIELD OF LAW IN INDONESIA - Titi Mubarokah (Qawwam : The Leader's Writing, 2025)
Islam is present as a religion of perfection through the prophetic treatise of the Prophet Muhammad PBUH which carries the mission of social transformation and the enforcement of justice. However, in the course of history, the treatise often faced resistance from the ummah, both in the early prophetic period and in the modern context through the rejection of legal regulation, especially Islamic family law. A similar phenomenon can be seen in the implementation of Law Number 1 of 1974 concerning Marriage in Indonesia, which until now still causes debate and rejection in the community. This study aims to identify the factors behind the people's rejection of prophetic treatises, analyze the form and reasons for the community's rejection of family law laws and regulations, and find the relevance and relationship between the two phenomena. The results of the study show that such resistance is generally rooted in a strong attachment to ancestral traditions and values, as well as the unpreparedness of society to accept social change and legal reforms. Some of the family law issues that often cause rejection include interfaith marriage, the recognition of children out of wedlock, and provisions regarding the legal requirements for marriage. This study concludes that a more inclusive, dialogical, and educational approach is needed in the process of reforming and implementing Islamic family law. This approach is expected to be able to bridge the tension between old traditions and the need for legal reform, thereby creating social harmony and substantive justice in society.